C6 Coefficients for Interacting Rydberg Atoms and Alkali-Metal Dimers - Herrera-Urbina, F (American Physical Society, 2020)
We study the van der Waals interaction between Rydberg alkali-metal atoms with fine structure (n2Lj; L≤2) and heteronuclear alkali-metal dimers in the ground rovibrational state (Xς+1; v=0, J=0). We compute the associated C6 dispersion coefficients of atom-molecule pairs involving Cs133 and Rb85 atoms interacting with KRb, LiCs, LiRb, and RbCs molecules. The obtained dispersion coefficients can be accurately fitted to a state-dependent polynomial O(n7) over the range of principal quantum numbers 40≤n≤150. For all atom-molecule pairs considered, Rydberg states nSj2 and nPj2 result in attractive 1/R6 potentials. In contrast, nDj2 states can give rise to repulsive potentials for specific atom-molecule pairs. The interaction energy at the LeRoy distance approximately scales as n-5 for n>40. For intermediate values of n?40, both repulsive and attractive interaction energies of the order of 10-1000μK can be achieved with specific atomic and molecular species. The accuracy of the reported C6 coefficients is limited by the quality of the atomic quantum defects, with relative errors ΔC6/C6 estimated to be no greater than 1% on average. © 2020 American Physical Society.